Continued Use of Food Delivery Applications (FDAs) Post COVID-19 in Malaysia: Barriers and Growth - Masilah, Mohamad; Rahayu, Tasnim; Siti Aisyah, Binti Ya'kob (e-IPH, 2023)
COVID-19 has opened many prospects for the retail sector, especially the food industry. Due to the pandemic retrenchment, the online channel has played a crucial role in ensuring the business's survival. Nevertheless, companies face several issues concerning Food Delivery Applications (FDAs), primarily related to user intent and barriers to non-adoption. The study aims to analyze the factors that influence user intent to use FDAs continuously, discover the barriers that influence consumers' intention to use FDAs, and explore the potential growth of FDAs.